Yin Yang 1 Plays an Essential Role in Breast Cancer and Negatively Regulates p27 - Wan, Meimei (American Society for Investigative Pathology, 2012)
Yin Yang 1 (YY1) is highly expressed in various types of cancers and regulates tumorigenesis through multiple pathways. In the present study, we evaluated YY1 expression levels in breast cancer cell lines, a breast cancer TMA, and two gene arrays. We observed that, compared with normal samples, YY1 is generally overexpressed in breast cancer cells and tissues. In functional studies, depletion of YY1 inhibited the clonogenicity, migration, invasion, and tumor formation of breast cancer cells, but did not affect the clonogenicity of nontumorigenic cells. Conversely, ectopically expressed YY1 enhanced the migration and invasion of nontumorigenic MCF-10A breast cells. In both a monolayer culture condition and a three-dimensional Matrigel system, silenced YY1 expression changed the architecture of breast cancer MCF-7 cells to that resembling MCF-10A cells, whereas ectopically expressed YY1 in MCF-10A cells had the opposite effect. Furthermore, we detected an inverse correlation between YY1 and p27 expression in both breast cancer cells and xenograft tumors with manipulated YY1 expression. Counteracting the changes in p27 expression attenuated the effects of YY1 alterations on these cells. In addition, YY1 promoted p27 ubiquitination and physically interacted with p27. In conclusion, our data suggest that YY1 is an oncogene and identify p27 as a new target of YY1.